Peningkatan Kapasitas dan Kompetensi Pengawas Kecamatan Se-Kabupaten Kolaka Pada Pemilihan Serentak Tahun 2024 - Ananda, Adhe Ismail; Ar, Sulkifli; Fatmawati (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
The District Election Supervisory Committee (Panwascam) has an important role in determining the quality of elections at the sub-district level. Based on the experience of previous elections, it is still found that Panwascam has not been maximized in carrying out its duties, authorities, and obligations as stipulated in laws and regulations. Therefore, community service was carried out in the form of a briefing carried out by the Bawaslu of Kolaka Regency, by presenting the Author as a Resource Person. This activity uses a lecture method, supported by media such as laptops and LCDs to convey material in the form of duties, authorities, and obligations of Panwascam in accordance with Law Number 7 of 2017 concerning Elections and other technical regulations so that Panwascam can work effectively. The results of this activity include three main things. First, Panwascam in Kolaka Regency in general has understood their duties, authorities, and obligations so that they are able to carry out supervision of the 2024 Simultaneous Elections properly. Second, this activity motivates Panwascam to carry out direct, public, free, confidential, honest, and fair supervision. Third, regular technical guidance is needed with a focus on general supervision and supervision of each stage of the election so that the implementation of supervision of the 2024 Simultaneous Elections becomes better and more effective.